2015
DOI: 10.1093/jb/mvv065
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis study to disrupt electrostatic interactions on the twofold symmetry interface ofEscherichia colibacterioferritin

Abstract: Ferritins and other cage proteins have been utilized as models to understand the fundamentals of protein folding and self-assembly. The bacterioferritin (BFR) from Escherichia coli, a maxi-ferritin made up of 24 subunits, was chosen as the basis for a mutagenesis study to investigate the role of electrostatic intermolecular interactions mediated through charged amino acids. Through structural and computational analyses, three charged amino acids R30, D56 and E60 which involved in an electrostatic interaction n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 26 publications
5
20
0
Order By: Relevance
“…Native PAGE electrophoresis was performed to further confirm the oligomerization preference of the designed mutants. Consistent with the SEC experiment, only the D132W mutant formed two bands, corresponding to the 24-mer and dimer [ 16 , 17 , 18 ]. All the other mutants generated bands corresponding to wild-type dimer ( Figure 3 ).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Native PAGE electrophoresis was performed to further confirm the oligomerization preference of the designed mutants. Consistent with the SEC experiment, only the D132W mutant formed two bands, corresponding to the 24-mer and dimer [ 16 , 17 , 18 ]. All the other mutants generated bands corresponding to wild-type dimer ( Figure 3 ).…”
Section: Resultssupporting
confidence: 66%
“…Our studies have demonstrated the possibility of altering the distribution of 24-mer cage and dimer states through single-point mutations [ 16 , 17 , 18 ]. In one of these studies, we showed that computationally designed symmetric aromatic interactions are able to extend the interaction networks across protein–protein interfaces and shift the oligomerization of BFR towards the cage state [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, destabilization in favor of dimers has led to decreased thermal stability in mycobacteria ferritin, 45 E. coli ferritin A, 15 Dps, 10 and E. coli bacterioferritin. 11 For wt AfFtn, the T m in low-salt conditions was found to be essentially the same as that in high-salt, indicating that stability of the dimer is very similar to that of the assembled cage and that 24mer assembly does not increase the stability of the dimer. 21 However, in E. coli bacterioferritin, mutations designed to plug an interdimer water pocket with hydrophobic residues led to significantly enhanced thermal stability (Δ T m >20 °C) but greater dimer population compared to the wt, as the geometry of the more stable dimers prevented cage formation.…”
Section: Discussionmentioning
confidence: 81%
“…This modular assembly can be used to bind QDs, metal, and magnetic nanoparticles for immunofluorescence, electron microscopy, and Magnetic Resonance Imaging (MRI) [57]. The ability of ferritin nanocages to naturally encapsulate ~4500 iron atoms [26,60] and the possibility to display fluorescent proteins were exploited for enhanced detection of tumors [20,26]. Matsumoto and coworkers engineered Fn PNPs to increase iron uptake by 3-fold, which resulted in a five-fold enhancement in the MRI imaging resolution [27].…”
Section: Biosensing and Bioimaging Applications Of Pnpsmentioning
confidence: 99%